The Relationship Between Murabahah And Musyarakah Financing And Profitability: A Case Study Of BMT Hasanah - Syamsul Arifin; Alifiani Hidayatus Sholekhah; Rokhmah Nur Jannah; Devangga Putra Adhitya Pratama; Kurniawati Kurniawati; Mahmud Ismail (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2025)
This study aims to describe the effect of murabahah and musyarakah mutanaqishah financing on the effectiveness of BMT Hasanah's profit earning during the covid-19 pandemic. This research method uses quantitative methods, data collection techniques used are documentation techniques. The data analysis technique used is multiple linear regression technique. The results of this study based on a partial test showed that murabahah financing had no effect on BMT Hasanah profits, while musyarakah mutanaqishah financing had a negative effect on BMT Hasanah profits. Then the results of the simultaneous test show that murabahah and musyarakah mutanaqishah financing have a simultaneous positive effect on BMT Hasanah's profit.Simultaneously both have an effect on ROA. Shows the results of the R square value of 0.984.